Proceedings of the Workshop on Human-Computer Question Answering 2016
DOI: 10.18653/v1/w16-0102
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing for (almost) Real-time Question Answering

Abstract: Modern search engines have made dramatic progress in the answering of many user's questions about facts, such as those that might be retrieved or directly inferred from a knowledge base. However, many other questions that real users ask are more complex, such as asking for opinions or advice for a particular situation, and are still largely beyond the competence of the computer systems. As conversational agents become more popular, QA systems are increasingly expected to handle such complex questions, and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…All the answers were randomly shuffled and rated on a scale from 1 (bad) to 4 (excellent) by workers hired on Amazon Mechanical Turk 8 . Existing research demonstrated, that such crowdsourced labels correlates well with the official ratings, provided by the professional NIST assessors (Savenkov, Weitzner, and Agichtein 2016). Each answer was labeled by 3 different workers, and we averaged the scores to get the final quality labels for the candidates.…”
Section: Answer Quality Evaluationmentioning
confidence: 93%
See 1 more Smart Citation
“…All the answers were randomly shuffled and rated on a scale from 1 (bad) to 4 (excellent) by workers hired on Amazon Mechanical Turk 8 . Existing research demonstrated, that such crowdsourced labels correlates well with the official ratings, provided by the professional NIST assessors (Savenkov, Weitzner, and Agichtein 2016). Each answer was labeled by 3 different workers, and we averaged the scores to get the final quality labels for the candidates.…”
Section: Answer Quality Evaluationmentioning
confidence: 93%
“…Instead of immediately returning the answers, CRQA sends questions and top-7 ranked candidates to crowd workers and waits for the responses. We chose to give 7 answers based on the average number of rated answers in our preliminary studies (Savenkov, Weitzner, and Agichtein 2016). Since in TREC LiveQA systems had only 60 seconds to answer each Figure 3: User Interface for workers in our Crowd-Powered Question Answering system question, we start a timer when a question arrives, and the system waits to receive all worker contributions until the timer reaches 50 seconds to leave some time to generate the final answer.…”
Section: Crowdsourcing Modulementioning
confidence: 99%
“…Afterwards, translation probabilities were computed via IBM and Hidden Markov Models to obtain the likelihood of an answer being the translation of the question. Savenkov et al (2016) presented a system that could be used to filter or re-rank the candidate answers by providing validation for the answers. They specifically focused on knowing the effect of time restrictions in the close real-time QA setting, thereby developing a way in which crowd will be able to create the answer candidates directly within a limited amount of time and also the way in which crowd will be able to rank sets of given answers to a question within a specified amount of time.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, we leverage on the fact that the performance of the crowd workers determines the quality of the result of a crowdsourcing task, and hence the need to develop an effective and reliable question answering system that is capable of validating and evaluating the answers provided by the crowd because of their varying reliability as established in past works (Hung et al, 2017;Savenkov et al, 2016). All these are important issues to be addressed in Artificial Intelligence.…”
Section: Related Workmentioning
confidence: 99%
“…Non-task oriented dialogues contribute to continuing conversations with users [1][2] and to building human social relationships [3]. There are two main methods for developing non-task oriented dialogue systems: a machine learning approach [4][5][6] and a rule-based one [7][8]. The former approach generally requires large corpus data.…”
Section: Introductionmentioning
confidence: 99%